Unraveling the dual character of sulfur atoms in a series of Hg(ii) coordination polymers containing bis(4-pyridyl)disulfide12. Issue 14 (23rd March 2017) - Azhdari Tehrani, Alireza; Ghasempour, Hosein; Morsali, Ali; Bauzá, Antonio; Frontera, Antonio; Retailleau, Pascal
Abstract : A dual behavior of the S atom, as a Lewis acid and as an electron donor, is observed in Hg(ii ) coordination compounds. Abstract : Chalcogen bonding interactions have earned an important recognition as prominent driving forces in fields such as supramolecular chemistry and crystal engineering. Herein, three Hg(ii ) coordination polymers containing bis(4-pyridyl)disulfide were synthesized and characterized by X-ray crystallography and spectroscopic techniques. The crystal packing of these compounds was analyzed using different geometrical, statistical and theoretical analyses. A dual behavior of the S atom is observed in these compounds, since it is able to act as a Lewis acid in S⋯X chalcogen bonding and also participate in lp⋯π interactions as an electron donor.